Optimized Production of High Purity Sulphuric Acid via Contact Process - Thlama Mperiju; Tome Sylvain; Moses NyoTonglo Arowo; Tilak Dhanda; Abdulhalim Abubakar; Babakaumi Ahmadu Goriya; Aminullah Zakariyyah Abdul (Logistic and Operation Management Research (LOMR), 2023)
Sulphuric acid (H2SO4) is of immense importance to the chemical industry and humanity. The use of Aspen Plus modeling, simulation, and optimization via the contact process has enabled the production of grade sulphuric acid. Notably, the research findings highlight the sensitivity of water flow rate to the maximization of H2SO4 production. Through these methods, a production capacity of around 8 tons per day was achieved, with a purity level of 98.9%. This achievement significantly contributes to meeting the demand for sulphuric acid in various industries. Moreover, exploring alternative sourcing methods, such as utilizing elemental sulphur, offers the potential for further optimizing H2SO4 production. The benefits of improving H2SO4 production extend beyond the chemical industry. Sulphuric acid finds applications in agriculture, petroleum refining, pharmaceuticals, and metal processing. Enhancing the production process ensures a reliable supply for these sectors. In summary, sulphuric acid is indispensable to the chemical industry and humanity at large. Aspen Plus modeling and optimization techniques have successfully improved the production of high-grade sulphuric acid, resulting in increased capacity and purity. Exploring alternative sourcing methods further enhances production possibilities. These advancements have wide-ranging implications, benefiting multiple industries and driving progress in sectors reliant on sulphuric acid.